The possibility of an island; or, The double bind of Houellebecq’s apocalypse: when the end is not the end - E. Snyman (Literator, 2008)
The purpose of this article is to demonstrate that “The possibility of an island” (2005), the latest novel by the controversial French author Michel Houellebecq, utilises a variety of so-called marginal genres such as millennial, apocalyptic, Utopian writing and science fiction to question and to continue the millennial project he elaborated in “Atomised” (2001). The latter novel, first published in French in 1998, explores the idea of a new order that would gradually come into existence during the new millennium, namely that of a neo-humanity produced through cloning. In “The possibility of an island” this Utopian construction turns unequivocally into a dystopia. This novel thus adds a double bind to the Apocalypse foreseen in “Atomised”: the end was not the end, but just the beginning of an intermediary phase.This analysis of Houellebecq’s novelistic techniques is based on theoretical descriptions of the genres on which the two novels draw, as well as narratological concepts formulated by Roland Barthes and Gérard Genette. The conclusion of the article points out that Houellebecq’s utilisation of marginal genres enables him to question contemporary civilisation and to investigate the consequences of scientific research on future generations.